Controlled Disassembly of Elemental Sulfur: An Approach to the Precise Synthesis of Polydisulfides. (18th February 2022) - Chao, Ji‐Yan; Yue, Tian‐Jun; Ren, Bai‐Hao; Gu, Ge‐Ge; Lu, Xiao‐Bing; Ren, Wei‐Min
Abstract: The usage of elemental sulfur (S8 ) for constructing sulfur‐containing polymers is of great significance in terms of sulfur resource utilization or fabrication of high‐performance polymers. Currently, the random disassembly of S8 hinders its direct use in the precise synthesis of sulfur‐containing polymers. Herein, we provide an effective strategy for controlling the dismantlement of S8 to synthesize polydisulfides, a promising category of dynamic bonds containing polymers. In this strategy, the completely alternating copolymerization of one sulfur atom, which is orderly derived from S8, with episulfides is achieved with MTBD (7‐methyl‐1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene) as catalyst and [PPN]SbF6 ([PPN] + is bis(triphenylphosphine)iminium) as cocatalyst. Delightedly, the living‐ polymerization feature, and the good monomer compatibility allows for the access to diverse polydisulfides. Furthermore, the density functional theory (DFT) was employed to elaborate the copolymerization process. Abstract : A strategy for controlling the orderly disassembly of elemental sulfur (S8 ) in the presence of MTBD (a hindered organic base) and [PPN]SbF6 (an ammonium salt) is described for constructing polydisulfides by copolymerizing with episulfides. The "living polymerization" feature and good monomer compatibility of this copolymerization allows for the access to diverse polydisulfides with well‐defined structures and excellent optical properties.